Ubisoft’s Notre-Dame: Digital Gaming for Material Heritage’s Sake - Hanussek, Benjamin (Loading)

(untitled) (Canadian Game Studies Association, 2024)
In 2019, the Notre-Dame de Paris was devastated by a fire. The importance of the Notre-Dame as world heritage was underlined by the countless contributions, donations and solidarity all around the world that pledged to help to rebuild the cathedral. Among all contributions Ubisoft’s idea to offer its game Assassin's Creed: Unity for free to the public was arguably most celebrated as innovative and creative measure to secure heritage in case of its destruction. This case opens up new perspectives and roles of heritage management as also the development and distribution of video games in the twenty first century. The case of Ubisoft’s Notre-Dame is discussed in this paper under a comparative analysis to the game Never Alone and a critical inquiry towards the benefits, consequences and repercussions of the growing importance of synchronising heritage protection with video game production. Also, the perceptive aspect of connecting to heritage as player through a game and its spatial aspects will be explained under Chapman’s concept of narrative gardens.